2022
DOI: 10.3390/ma15051970
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Patient-Specific Polymethylmethacrylate Cranial Implants for Virtual Surgical Planning: An In-Vitro Study

Abstract: Cranioplasty with freehand-molded polymethylmethacrylate implants is based on decades of experience and is still frequently used in clinical practice. However, data confirming the fracture toughness and standard biomechanical tests are rare. This study aimed to determine the amount of force that could be applied to virtually planned, template-molded, patient-specific implants (n = 10) with an implant thickness of 3 mm, used in the treatment of a temporoparietal skull defect (91.87 cm2), until the implant crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…6 While PSIs can provide smother cosmetic results than freehand PMMA implants, their process of manufacturing is time-consuming and expensive. 8 The demand for cost-effective patient-specific treatment led to a hybrid manufacturing process, with in-house silicon mold production used to produce accurate intraoperative PMMA implants. 9 Since August 2023, both implant types can now be manufactured at the point-of-care using the patient's preoperative CT or MRI imaging data for virtual planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 While PSIs can provide smother cosmetic results than freehand PMMA implants, their process of manufacturing is time-consuming and expensive. 8 The demand for cost-effective patient-specific treatment led to a hybrid manufacturing process, with in-house silicon mold production used to produce accurate intraoperative PMMA implants. 9 Since August 2023, both implant types can now be manufactured at the point-of-care using the patient's preoperative CT or MRI imaging data for virtual planning.…”
Section: Discussionmentioning
confidence: 99%
“…Polymethylmethacrylate (PMMA) is mainly used in intraoperative freehand techniques, whereas industrially manufactured PSIs are often made from titanium or polyetheretherketone (PEEK) 6 . While PSIs can provide smother cosmetic results than freehand PMMA implants, their process of manufacturing is time-consuming and expensive 8 . The demand for cost-effective patient-specific treatment led to a hybrid manufacturing process, with in-house silicon mold production used to produce accurate intraoperative PMMA implants 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have introduced workflows for implant fabrication to facilitate facial reconstruction, considering feasibility, cost-effectiveness, force resistance, and accuracy [ 27 , 32 , 37 , 38 ]. While patient-specific implants provide significant time-saving benefits during surgery by eliminating the need for manual adjustments such as bending, it is essential to consider the potential for inaccuracies in their fabrication.…”
Section: Discussionmentioning
confidence: 99%
“…Their study illustrated that utilising a 3D reconstruction method and PEEK material would minimise time-consuming alterations while also improving the implant's fit, stability, and strength. Msallem et al 27 demonstrated that an implant thickness of 3 mm for a temporoparietal skull defect can withstand sufficient force to protect the brain. Greater implant weight and, therefore higher material content increases thickness, resulting in greater resistance.…”
Section: Introductionmentioning
confidence: 99%